The Torah of the Gospel: A Rabbinic Polemic against The Syro-Roman Lawbook - Paz, Yaḳir (Harvard theological review, 2019)
In a famous story in b. abb. 116a-b, Imma Shalom and her brother, Rabban Gamaliel, present to a philosopher a dispute concerning the inheritance of the daughter. The judge, having being bribed by Imma Shalom, rules in her favor, against the ruling of the Torah of Moses, arguing that the latter has been abrogated and replaced by the "Torah of the Gospel," which states that "the son and the daughter inherit equally." After being bribed by Rabban Gamaliel, the philosopher recants, citing Matt 5:17, where Jesus reaffirms the validity of the Mosaic Law.This article argues that the "Torah of the Gospel" actually refers to The Syro-Roman Lawbook, and that the story is constructed as a response to a radical and new legal supersessionist argument brought forth in this book which is directly linked to the Roman law of equal inheritance. This is the first clear evidence we have that, alongside the New Testament, the Babylonian rabbis also read and engaged directly with Christian books of their time written in Syriac. This has major ramifications on the way we perceive the textual culture of the Babylonian rabbis and their intellectual interactions with East Syrians.